Study on prevalence of left ventricular diastolic dysfunction in chronic obstructive pulmonary disease - Rafi, Mohamed; Jaber, Monna Mohamed (International Journal of Advances in Medicine, 2019)
Background: Left ventricular diastolic dysfunction (LVD) is very common in chronic obstructive pulmonary disease (COPD) patients. The aim of the present study was to LVD function in COPD patients using echocardiogram and to detect the presence of LVD dysfunction in all stages of COPD. Methods: This was an observational study done at Institute of Internal Medicine, Madras Medical College and Rajiv Gandhi Government General Hospital, Chennai, during the period from March 2015 to August 2015. The study included 100 patients with COPD. All patients were subjected to chest X-ray, electrocardiogram, pulmonary function test (PFT) and echocardiogram. Results: The results showed the prevalence rate of LVD dysfunction in 80% patients with COPD. There was a good significant correlation between age (p<0.001), status of smoking (p<0.05), chest X-ray findings (p<0.001) and stages of COPD (p<0.001) with incidence of LVD in study population. Conclusions: High prevalence of LVD dysfunction was noticed in patients with COPD. Hence patients with COPD should undergo routine examinations timely to prevent the incidence of associated cardiovascular complications.